Analyzing roles, challenges and opportunities the participants of “campus teaching program” in elementary school - Kartasasmita, Saepudin; Hariyanti , Hariyanti; Handayani , Dini; Istianah , Anif; Permady, Gigieh Cahya; Sari , Filma Alia (Universitas Ahmad Dahlan, 2024)
This article aims to describe How the roles, challenges, and opportunities of students who participate in campus programs teaching batches 3,4 and 6. Research conducted in Riau Province on 15 participants students, 4 Supervisors Field (DPL) head schools, and several teachers' councils school the basis on which school target. Research was done on a range time February 2022 to December 2023. Research data was collected through interviews and study documentation. Data analysis techniques using the Miles and Huberman model which consists of data collection, data verification and reduction, and data extraction conclusion. As for the triangulation technique use a triangulation data source. Research results find that there are a number of roles students as participants in campus teaching, namely; (1) planners, students discuss with DPL and supervising teachers For designing programs and strategies that will done at school target during the period of service; (2) implementer, during less than 4 months serve, then the program is about literacy numeracy, adaptation technology, and arrangement administration carried out by participants by creating a timeline so that all programs can be implemented effectively and appropriately​ time; (3) evaluator, participant do evaluation through pre-test and post-test AKM class for see condition beginning condition literacy numeracy in schools and conditions end after given assistance through implementation of campus programs teaching. The challenges faced by students are; (1) the location of the school's distant and remote targets; and (2) the Semester Credit System conversion system which is ambiguous. The chances include (1) campus teaching is a national program so that Power the recipient is more-big; (2) giving experience and expanding connection to students outside​ life campus; (3) getting incentives and assistance.